Sida : la politisation d’une épidémie [1984] - Dennis Altman (Genre, Sexualité et Société)
The considerable attention that has been paid to Aids in the United States since 1983 can be explained by several factors. However, much of the response to the epidemic had to do with the strong connection the latter established between “sexual excess” and death, and above all, between homosexuality and illness. This article insists on the pre-existing conditions and prejudices that have allowed Aids to be defined as a “gay disease” and analyses the impact of such a definition in three fields : the medical, the political and the sexual. While he acknowledges the heavy burden paid by gay males to the epidemic as well as their unique ability to come together as a community to fight it, the author considers the conceptual link between aids and gays to be both misleading and dangerous. After criticizing temptations among the gay movement to pose as victims, he also warns against the risks of scapegoating and greater surveillance of the gay population. Finally, he calls for a “deshomosexualization” of Aids so that the discussion may shift to one that sees the epidemic as primarily a medical and health care issue.